Heritage is not a museum piece (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2018)
This article reflects about the registration of different traditional puppettheatre manifestations as intangible cultural heritage. It discusses how important it is to preserve traditional puppetry but also presents doubts about how the registration affects this art form that is constantly changing.Keywords: Cultural heritage. Puppet theatre. Traditional puppet theatre.